2017
DOI: 10.2196/jmir.7135
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Active Ingredients of eHealth Interventions Targeting Persons With Poorly Controlled Type 2 Diabetes Mellitus Using the Behavior Change Techniques Taxonomy: Scoping Review

Abstract: BackgroundThe behavior change technique taxonomy v1 (BCTTv1; Michie and colleagues, 2013) is a comprehensive tool to characterize active ingredients of interventions and includes 93 labels that are hierarchically clustered into 16 hierarchical clusters.ObjectiveThe aim of this study was to identify the active ingredients in electronic health (eHealth) interventions targeting patients with poorly controlled type 2 diabetes mellitus (T2DM) and relevant outcomes.MethodsWe conducted a scoping review using the BCTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 89 publications
(124 reference statements)
7
35
0
2
Order By: Relevance
“…We identified 20 out of a possible 93 BCTs across all studies, indicating that less than a quarter of the available BCTs are commonly used in interventions to improve ED discharge communication. This low percentage of identified BCTs is consistent with other reviews of BCTs in diabetes care [17,66] and medication adherence literature [67].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We identified 20 out of a possible 93 BCTs across all studies, indicating that less than a quarter of the available BCTs are commonly used in interventions to improve ED discharge communication. This low percentage of identified BCTs is consistent with other reviews of BCTs in diabetes care [17,66] and medication adherence literature [67].…”
Section: Discussionsupporting
confidence: 88%
“…This is not surprising as discharge communication is meant to instruct patients and caregivers on how to perform behaviours specific to managing care of their child at home. This finding is also consistent with BCTs identified in the diabetes [17,66], cardiovascular disease [68], and physical activity [69] literature. Interestingly, many of the common BCTs used to address other health behaviours,, including action planning [67], goal setting [66,68,70], self-monitoring of behaviours [67,[69][70][71], problem solving [70,72] and reducing negative emotions [68,70] have not been widely used in discharge communication interventions to date.…”
Section: Changing Patient/caregiver Behaviourssupporting
confidence: 90%
See 1 more Smart Citation
“…We identi ed 20 out of a possible 93 BCTs across all studies, indicating that less than a quarter of the available BCTs are commonly used in interventions to improve ED discharge communication. This low percentage of identi ed BCTs is consistent with other reviews of BCTs in diabetes care [17,66] and medication adherence literature [67].…”
Section: Discussionsupporting
confidence: 87%
“…The BCTTv1 includes 93 individual techniques with labels and de nitions organized into 16 BCT categories [10]. The BCTTv1 has been used to evaluate and design a number of health care interventions in varying clinical settings, including medication adherence [11], weight management [12], physical activity [13,14], antimicrobial resistance [15], and diabetes care [16,17]. Previous research has found the BCTTv1 to be a useful tool for classifying intervention components and standardizing intervention language [15][16][17][18].…”
Section: Combining Both Intervention Classi Cation and Health Behaviomentioning
confidence: 99%